Evaluation of osseous regeneration in alveolar distraction osteogenesis with histological and radiological aspects - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2007)
Purpose: Alveolar distraction osteogenesis is used for reconstruction of defects caused by trauma, periodontal disease, or congenital anomalies of the dentoalveolar region. P atients and Methods: Alveolar distraction osteogenesis was performed on 10 patients with various vertical alveolar defects in the mandible. Panoramic radiographs and computed tomography (CT) scans were obtained preoperatively. At the end of 12 weeks, panoramic radiographs and dental CT scans were taken and the bony specimens were harvested from the distracted areas by trephine bur for histologic evaluation. After a year, the status of the distraction areas was assessed by radiographs and dental CT scans. Densities of the newly formed bone were evaluated at the twelfth week and the first year by dental CT scans. Results: At the twelfth week, tubular bone was longitudinally oriented and osteoblastic activation was increased; the osseous density in the distraction chamber was higher than the original medullary bone density, which increased from the twelfth week to the first year. The regenerated bones were more dense (866.81) than the pre-existing medullary bone (309.66), and less dense than the pre-existing cortical bone (1641.12) at the twelfth week. Bone densities were seen to have increased gradually by the end of the first year (1089.99). Conclusion: Alveolar distraction osteogenesis can be used successfully for reconstruction of alveolar bone deficiencies caused by trauma or periodontal defects. (C) 2007 American Association of Oral and Maxillofacial Surgeons.
Keywords: RIDGE AUGMENTATION; TRABECULAR BONE; IMPLANTS; DEFECTS; DENSITY